Repurposing Autodesk Civil 3D grading tools for natural landform closure design - Buechler, C; Ludwick, D; Pelletier, JD; Abramson, N; Chataut, S (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
In mine closure projects, the term landform typically refers to the shape of a facility that is intended to mimic the natural forms of the surrounding stable topography. In arid climates, natural landform shapes may be chosen to increase the erosional stability of the final design. Closure of mine facilities can result in long slope lengths (>240 m) that are exceptionally prone to erosional damage from rainfall. Structural closure strategies of the past have utilized systems of benches and channels to break up long slope lengths, which may pose a long-term risk in some settings. Instead, a convex-concave slope can be utilized to mitigate the erosional risks of long slope lengths through gradual grade changes. To apply these principles to the closure of a tailings dam, this study selected a convex-concave profile to create a three-dimensional (3D) landform that protects an exposed dam face from degradation. However, designing natural landform shapes using typical 3D drafting tools can be a challenge. Traditional grading tools used in 3D drafting software are well-suited for creating straight lines, constant slope gradients, and angular corners. These linear tools can be at odds with evolving thinking in mine closure that is trending toward more natural and geomorphic shapes. Here we describe the methods used to create a 3D landform design surface in Autodesk Civil 3D (Civil 3D). Corridors in Civil 3D typically follow similar rules, utilizing linear slopes and sharp grade changes within subassemblies to create corridor elements, such as sidewalks, curbs, and roadways. In our design, these corridor design tools were repurposed to create a curvilinear landform shape. This closure strategy was implemented on a tailings dam that consists of a main embankment and two wingwalls positioned at offset angles from the main embankment. To start, an alignment was positioned at the crest of the new landform to control the slope radii at the existing dam corners and to control the primary direction of surface water flow. A design profile was created to minimize variations in elevation and prevent flow convergences on the landform slope. A convex-concave slope profile was defined in Civil 3D, and a custom subassembly was created from the landform. The landform design surface was then created from the corridor utilizing subassembly codes and corridor feature lines. Through the creative application of Civil 3D design tools, we can create an innovative design surface for long-term mine closure.
Keywords: landform